Sistem Informasi Pengelolaan Stok Bahan Baku Roti secara Real-Time berbasis Web - Wulandari, Gilang Ayu; Riadi, Aditya Akbar; Susanto, Arief (Universitas Hamzanwadi, 2025)
Technological developments can improve efficiency in business management, including in UMKM Anna Bakery Guwo Tlogowungu which still uses manual recording in managing raw material stock, which can hinder the production process. This has the potential to cause errors in recording, data loss, financial losses, delays in stock information, and obstacles in decision-making. The purpose of this research is to design and develop an information system for managing bread raw material stock to increase productivity and operational efficiency. The system was developed using the waterfall method, which includes the stages of needs analysis, design, implementation, verification, and maintenance, with data collected through interviews and observations. System testing through the black box to ensure that the system functions in accordance with the provisions set. This system is built with PHP and MySQL and is equipped with authentication features to differentiate user access rights to maintain data security. The results of the study show that this system is able to accelerate stock recording by up to 70% compared to manual methods, reduce recording errors, and present reports accurately and in real time, and support flexible data updates at Anna Bakery.